Gender and Islam in Village Head Elections in Kudus Regency in 2022 - Setiadi, Ozi (POLITEA, 2023)
Gender relations and Islam occupy a distinctive space in the succession of village heads. This research will highlight gender relations with Islam and the involvement of female nationalists and Islamists in village head elections. This field research uses a qualitative research method of narrative data analysis. Data were obtained from unstructured interviews, documents, focus group discussions (FGD), and literature. This research found that there is a relationship between gender and Islam in the village head elections in Kudus Regency in 2022. This relationship can be seen from the involvement of Islamist and nationalist women in village head elections, as voters, candidates, to the success team. The conflict between adat and Islam which does not allow women to be involved in leadership succession, and even involved in the wider public sphere, is not a barrier. Kudus Regency women continue to respect Islam in the formal dimension, while gender equality between men and women is considered a form of justice.